2022
DOI: 10.1002/adfm.202201384
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Anchoring‐Induced Oriented Crystal Growth for High‐Efficiency Lead‐Tin Perovskite Solar Cells

Abstract: The narrow bandgap (≈1.2 eV) Pb-Sn alloyed perovskite solar cell is a promising bottom component cell for all-perovskite tandem devices that are expected to offer higher efficiency than the theoretical Shockley-Queisser limit of the single-junction solar cells. The density functional theory (DFT) study reveals that the Pb-Sn perovskite film with the (100) orientation would render significantly reduced trap density, which is a critical figure-of-merit for perovskite device performance. Alkyl diamine is therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 41 publications
1
61
0
Order By: Relevance
“…These ligands-anchored nuclei can serve as a surface template to successfully induce (100)-oriented crystal growth of Pb-Sn mixed perovskite (Figure 13D), resulting in a dramatically enhanced PCE of 20.03% from 16.23% for the control device. 114 Similarly, BA + and EA + cations have also been employed to achieve oriented growth of Sn and Pb-Sn perovskite films. 118,119 In addition, Liu et al 115 reported a soft template-controlled growth (STCG) method via introducing (adamantan-1-yl)methanammonium (ADMA) to modulate the nucleation and growth of all-inorganic CsPbI 3 perovskite.…”
Section: Amine Saltsmentioning
confidence: 99%
See 3 more Smart Citations
“…These ligands-anchored nuclei can serve as a surface template to successfully induce (100)-oriented crystal growth of Pb-Sn mixed perovskite (Figure 13D), resulting in a dramatically enhanced PCE of 20.03% from 16.23% for the control device. 114 Similarly, BA + and EA + cations have also been employed to achieve oriented growth of Sn and Pb-Sn perovskite films. 118,119 In addition, Liu et al 115 reported a soft template-controlled growth (STCG) method via introducing (adamantan-1-yl)methanammonium (ADMA) to modulate the nucleation and growth of all-inorganic CsPbI 3 perovskite.…”
Section: Amine Saltsmentioning
confidence: 99%
“…Furthermore, a commonly overlooked but important point is that different crystal facets might possess various intrinsic trap states because the chemical structure of different crystal facets changes with crystal orientation. 111,114,117 Exploring the relationship between crystal orientation and trap states would strengthen knowledge of the correlation between crystallization kinetics and carrier dynamics, which is conducive to a more comprehensive understanding of the carrier transport behavior in PSCs. Furthermore, it is also of great significance to explore facet-dependent stability considering that different crystal facets could present various degrees of chemical stability.…”
Section: Facet-dependent Optoelectronic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This undoubtedly indicates that ionic liquids control the growth of CsPbBr 3 crystal along [h00] direction. [47] In addition, the orientation degree highly depends on the anion species by obeying an order of Cl − > BF 4 − > PF 6 − > NO 3…”
mentioning
confidence: 99%